answers: 1

Register to add an answer

The time for answering the question is over

Answer:

Answer:

\begin{gathered} \frac{ \sqrt{3} - 1 }{ \sqrt{3} + 1 } \\ \\ = ( \frac{ \sqrt{3} - 1 }{ \sqrt{3} + 1 } )( \frac{ \sqrt{3} - 1 }{ \sqrt{3} - 1 } ) \\ \\ = \frac{ {( \sqrt{3} - 1)}^{2} }{3 - 1} \\ \\ = \frac{4 - 2 \sqrt{3} }{2} \\ \\ 2 - \sqrt{3} \\ \\ a = 2 \\ \\ b = 1 \\ \\ \end{gathered}

3

+1

3

−1

=(

3

+1

3

−1

)(

3

−1

3

−1

)

=

3−1

(

3

−1)

2

=

2

4−2

3

2−

3

a=2

b=1

443

Becker

For answers need to register.

Contacts

mail@expertinstudy.com

Feedback

Expert in study

About us

For new users

For new experts

Terms and Conditions